2010
DOI: 10.1017/s0007114510000395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet, sex and age on fatty acid metabolism in broiler chickens:n-3 andn-6 PUFA

Abstract: The PUFA metabolism in broiler chicken was studied through the whole body fatty acid balance method. Four dietary lipid sources (palm fat, Palm; soyabean oil, Soya; linseed oil, Lin; fish oil, Fish) were added at 3 % to a basal diet containing 5 % palm fat. Diets were fed to female and male birds from day 1 to either day 21 or day 42 of age. Birds fed the Lin diet showed a significantly higher 18 : 2n-6 accumulation compared with the other diets (85·2 v. 73·6 % of net intake), whereas diet did not affect 18 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 30 publications
8
42
3
Order By: Relevance
“…Information about the levels of fatty acids in the whole body of broiler chickens at the time of slaughter with regard to sex and the currently used modern hybrids is largely missing. For example (Poureslami et al 2010a) reported that sex has only a marginal effect on n-3 and n-6 PUFA metabolism and no effect on metabolism of SaFA and MUFA (Poureslami et al 2010b). In marked contrast to these earlier data, the results of our trial document the existence of effects of sex on FA levels.…”
Section: Originalcontrasting
confidence: 99%
“…Information about the levels of fatty acids in the whole body of broiler chickens at the time of slaughter with regard to sex and the currently used modern hybrids is largely missing. For example (Poureslami et al 2010a) reported that sex has only a marginal effect on n-3 and n-6 PUFA metabolism and no effect on metabolism of SaFA and MUFA (Poureslami et al 2010b). In marked contrast to these earlier data, the results of our trial document the existence of effects of sex on FA levels.…”
Section: Originalcontrasting
confidence: 99%
“…LA (C18:2) and ALA (C18:3) cannot be biosynthesized de novo, and are instead derived from the diet, and subsequently cannot be bioconverted to longer and more unsaturated LC-PUFAs. Further-more, arachidonic acid (C20:4) was found to be the major metabolite of dietary LA (C18:2) (Poureslami et al, 2010). Merino et al (2011) reported that genetic variation in the FADS gene cluster could alter desaturase activity in human subjects of Caucasian and Asian descent.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are not completely consistent with those of Dänicke et al (1997), who showed that broilers fed a soya oil-supplemented diet exhibited higher ATTD of organic matter, crude fat, protein, and AMEN, and had higher ATTD of C18: 2 n-6 and C18: 3 n-3. Similarly, Poureslami et al (2010) showed that broilers fed linseed oil (high C18:3 n-3) had higher apparent digestibility of C18:2 n-6 and C18: 3 n-3 acid than broilers fed palm oil. Conversely, Crespo and Esteve-Garcia (2002) showed that there were no differences between sunflower oil (mainly C18:2 n-6) and linseed oil (mainly C18:3 n-3) in the digestibility of fat and nitrogen.…”
Section: Pinteraction Walnut Oilmentioning
confidence: 91%